Relationship between two‐level space‐vector pulse‐width modulation and carrier‐based pulse‐width modulation in the over‐modulation region. Issue 1 (1st January 2014) - Fang, Hui; Feng, Xiaoyun; Song, Wensheng; Ge, Xinglai; Ding, Rongjun
Abstract : For low voltage motor drive applications, in order to enhance the utilisation rate of dc bus voltage and extend the operating boundary of induction motors, the modulation index is often extended from the linear modulation region to the over‐modulation region. The relationship between two‐level space‐vector pulse‐width modulation (SVPWM) and carrier‐based pulse‐width modulation (CBPWM) in the linear modulation region has been widely investigated and it was shown that the conventional SVPWM is a special type of CBPWM algorithm with zero sequence components injection. On the basis of that, this study focuses on investigating their relationship in the over‐modulation region. Firstly, the superposition principle is adopted to analyse the features of SVPWM algorithm in the over‐modulation region. Second, the modulating functions of CBPWM equivalent to SVPWM in the over‐modulation modes I and II are derived, respectively, which are on the basis of the CBPWM regular sampling rule. Theoretical analysis shows that SVPWM is a special type of CBPWM algorithm not only in the linear modulation region but also in the over‐modulation region, which provides a bidirectional bridge for the transformation between SVPWM and CBPWM in the full modulation region. Finally, the validity and effectiveness of the theoretical analysis are verified by simulation and experimental results.